La ricerca multidisciplinare, un filo che lega diversi saperi - Manno, Mauro; Deganello, Francesca; Liotta, Leonarda Francesca; Casaletto, Maria Pia; Mineo, Carmelo (Chimica nella Scuola, 2025)
The hundredth anniversary of the foundation of the National Research Council (CNR), the largest public research institution in Italy, was an opportunity to propose scientific and dissemination initiatives by public engagement throughout Italy. As part of the event “Open Doors at CNR – Palermo”, on October 13th, 2023, the authors of this work met high school students at the Research Area of the CNR in Palermo, to discuss and reflect on some meta-scientific aspects of the researchers work, on how modern scientific research is a multidisciplinary activity that links multiple fields, and on how both inter- and trans-disciplinarity favor frontier research and are fundamental in the education of high school students. A year after that round table, the reflections of this article are devoted to high school teachers, who want to deepen and introduce students to the themes of multi- and interdisciplinary approaches to research, the trans-disciplinarity of knowledge, the researcher’s profession and the research activities carried out for the benefit of society, environment and economy.